Comparative analysis of the complete chloroplast genome between tetraploidy and diploidy of Cyclocarya paliurus (Batal.) Iljinskaja. Issue 9 (2nd September 2021) - Qu, Yinquan; Wang, Qian; Yu, Yanhao; Fu, Xiangxiang
Abstract: Cyclocarya paliurus (Batal.) Iljinskaja, a monotypic species in Cyclocarya of Juglandaceae, is regarded as one of important medical plants in China. In order to reveal the alterations in chloroplast (cp) genome with nuclear genome duplication, we presented the complete cp genomes of C. paliurus, and firstly analyzed on the basis of ploidy type (tetraploid and diploid C. paliurus ). The total length of the cp genome of tetraploid and diploid C. paliurus is 160, 938 and 161, 105 bp, respectively. Both type genome consist of a large single-copy (LSC) region (90, 221 and 90, 391 bp), a small single-copy (SSC) region (18, 593 and 18, 590 bp), and an pair of invert repeats (IRs) regions (26, 062 and 26, 062 bp). Tetraploid and diploid plastid genome contain 132 and 137 genes, 87 and 88 protein-coding genes, 37 and 39 tRNA genes, and both eight rRNA genes, respectively. Closely phylogenetic relationship by analyzing 23 cp genomes suggests that tetraploid C. paliurus probably originated from diploid C. paliurus .